Resveratrol Attenuates High Glucose-Induced Osteoblast Dysfunction via AKT/GSK3β/FYN-Mediated NRF2 Activation - Yue Xuan; Jie Wang; Xiaohui Zhang; Jie Wang; Jiahao Li; Qingbo Liu; Guangping Lu; Mengjie Xiao; Ting Gao; Yuanfang Guo; Cong Cao; Ou Chen; et al. (Frontiers Media S.A., 2022)
Osteoblast dysfunction, induced by high glucose (HG), negatively impacts bone homeostasis and contributes to the pathology of diabetic osteoporosis (DOP). One of the most widely recognized mechanisms for osteoblast dysfunction is oxidative stress. Resveratrol (RES) is a bioactive antioxidant compound to combat oxidative damage. However, its role in the protection of HG-induced osteoblast dysfunction has not been clarified. Therefore, our study aimed to explore potential regulatory mechanisms of RES for attenuating HG-induced osteoblast dysfunction. Our results showed that osteoblast dysfunction under HG condition was significantly ameliorated by RES via the activation of nuclear factor erythroid 2-related factor (NRF2) to suppress oxidative stress. Furthermore, using Nrf2-shRNA and wortmannin, we identified that activation of NRF2 via RES was regulated by the AKT/glycogen synthase kinase 3β (GSK3β)/FYN axis.